In vitro cytotoxic activity of ferula assafoetida on osteosarcoma cell line (Hos crl) - Mohd Shafri, Mohd Affendi; Yusof, Fathin Athirah; Md Zain, Ahmad Zulkarami (Universiti Teknologi Malaysia, 2015)
Ferula assafoetida is a herb that has been used traditionally to treat rheumatism, broken bones and stomach illness. The aim of this research is to study the cytotoxicity of F. assafoetida as an anti-cancer agent. Briefly, resin of F. assafoetida was macerated with ethanol or methanol for 3 days. The mixtures were then filtered, concentrated and dried. The cytotoxicity of extracts on an osteosarcoma cell line, HOS CRL, was determined using MTT assay method. The results were analysed with Tukey’s test (p<0.05) showed that F. assafoetida extract has cytotoxic effect which is dependent on the type of solvent (methanol > ethanol) and concentration (higher methanolic content > lower methanolic content). In conclusion, extracts of Ferula assafoetida might possess cytotoxic activity which could be useful to be developed for an anti-cancer treatment.